Application of ISO 12913 Standard to Assess Urban Soundscapes: A Case Study on Poznań - Dumanowski, Jakub; Preis, Anna; Felcyn, Jan (Archives of Acoustics, 2026)
ISO 12913 standards provide a unified framework for describing and assessing soundscapes, however, the lack of a Polish translation has so far limited their practical use. This paper presents the first application of a validated Polish version of the ISO/TS 12913-2 perceptual attributes, enabling full cross-language comparability of results. Whereas Polish research has traditionally focused on noise annoyance and broad judgements of acoustic comfort or discomfort, we outline the complete ISO-compliant assessment procedure, which combines: a soundwalk, questionnaires and audio-visual recording. The study was conducted at eight diverse urban locations in Poznań, Poland. Participants rated the soundscapes using eight attributes: przyjemne, tętniące życiem, bogate w wydarzenia, chaotyczne, dokuczliwe, monotonne, ubogie w wydarzenia, spokojne. Each rating set is mapped to a point in the 2D pleasantness-eventfulness space defined in ISO/TS 12913-3, facilitating visual comparison of locations and the identification of design needs. Results reveal pronounced perceptual differences between spatial typologies and demonstrate that the standardized approach provides richer, multidimensional information about the acoustic environment than conventional noise indicators. The proposed methodology establishes a reference framework for Polish soundscape studies and can support the creation of more people-friendly urban acoustic environments.